2015
DOI: 10.18097/pbmc20156103363
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy fishing of gp120 on immobilized aptamer and its mass spectrometry identification

Abstract: A method of atomic force microscopy-based fishing (AFM fishing) has been developed for protein detection in the analyte solution using a chip with an immobilized aptamer. This method is based on the biospecific fishing of a target protein from a bulk solution onto the small AFM chip area with the immobilized aptamer to this protein used as the molecular probe. Such aptamer-based approach allows to increase an AFM image contrast compared to the antibody-based approach. Mass spectrometry analysis used after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In order for AFM to detect specific targets, the AFM probe has to be functionalized with a molecule of high affinity [33,167]. The force applied to break the chemical bond between the probe and the target molecule is quantitatively determined from the force-distance curve [168][169][170]. Previous studies have demonstrated that a silicon nitride cantilever tip functionalized with DNA aptamers and cyclo-RGD peptides is able to detect their cognate α-thrombin, IgE molecules, and integrin α5β1 with high accuracy upto ~90 % [33,171].…”
Section: Molecular Recognition Imagingmentioning
confidence: 99%
“…In order for AFM to detect specific targets, the AFM probe has to be functionalized with a molecule of high affinity [33,167]. The force applied to break the chemical bond between the probe and the target molecule is quantitatively determined from the force-distance curve [168][169][170]. Previous studies have demonstrated that a silicon nitride cantilever tip functionalized with DNA aptamers and cyclo-RGD peptides is able to detect their cognate α-thrombin, IgE molecules, and integrin α5β1 with high accuracy upto ~90 % [33,171].…”
Section: Molecular Recognition Imagingmentioning
confidence: 99%
“…53 At V = 1 mL, C v = 10 −13 M, S = 0.4 mm 2 , and h = 2 nm, the obtained concentration C vs was 1.25 × 10 −4 M, confirming the ability of this approach to overcome the sensitivity limitations of proteomic analytical methods. Furthermore, the proteins concentrated on the AFM chip surface can be identified using MS. 54,55 The ability to detect proteins present in biological fluid using a combination of AFM and MS methods has already been shown. 56 For example, using this technique, viral hepatitis C marker proteins are registered and identified in the blood serum of patients.…”
Section: Future Strategies To Resolve the Human Proteomementioning
confidence: 99%
“…At V = 1 mL, C v = 10 –13 M, S = 0.4 mm 2 , and h = 2 nm, the obtained concentration C vs was 1.25 × 10 –4 M, confirming the ability of this approach to overcome the sensitivity limitations of proteomic analytical methods. Furthermore, the proteins concentrated on the AFM chip surface can be identified using MS. , …”
Section: Introductionmentioning
confidence: 99%
“…The identification of surfaceanchored proteins is a separate area of proteomic analysis that is of great significance for biotechnology and bioengineering with regards to the investigation of the functional properties of surface-localized biosystems. Developed surfaces, such as chromatographic columns [2] and microbeads [3], as well as planar surfaces [4,5], in particular atomically smooth ones [6,7], can be considered in this respect.…”
Section: Introductionmentioning
confidence: 99%